Transformational Leadership In The Coaching Profession: A Literature Review In The Context Of Athlete Coaching - Muhammad Ishak (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Transformational leadership has emerged as a critical component in modern sports coaching, as coaches are expected not only to improve athletic performance but also to support athletes’ psychological, social, and personal development. However, the effectiveness of transformational leadership within athlete development systems requires comprehensive synthesis and evaluation. Therefore, this study aimed to analyze the role of transformational leadership in the coaching profession and its contribution to athlete development from both conceptual and empirical perspectives. This study employed a Systematic Literature Review (SLR) approach by examining scientific publications indexed in Scopus, Web of Science, PubMed, SINTA, Google Scholar, and Garuda databases published between 2015 and 2025. The article selection process followed PRISMA guidelines. An initial search identified 186 articles, of which 25 studies met the inclusion criteria and were included in the final analysis. The findings revealed that transformational leadership positively influenced athlete motivation (88%), team cohesion (80%), psychological well-being (72%), and athletic performance (68%). Furthermore, transformational coaching behaviors enhanced athlete satisfaction, self-efficacy, commitment to training, and athlete retention. Inspirational motivation emerged as the most influential dimension, followed by individualized consideration, idealized influence, and intellectual stimulation. Conceptually, the findings support Transformational Leadership Theory, Self-Determination Theory, Social Identity Theory, and Athlete-Centered Coaching frameworks. In conclusion, transformational leadership represents a strategic coaching competency that contributes significantly to sustainable athlete development and long-term sporting success. Its integration into coach education and athlete development programs is strongly recommended.